A branquitude na obra “A integração do negro na sociedade de classes” de Florestan Fernandes: uma releitura crítica dos estudos raciais no Brasil - Martins, Luísa Paim (2023)
The studies that bring whiteness as an object of research problematize issues beyond the social, economic and symbolic privileges granted to individuals of white racial belonging: whiteness links itself to a way of understanding and classifying the world, which finds its roots in the colonial project. Historically, the white racial group has kept under its domain a discursive advantage; therefore, the very way that racial relations have been seized within this field of study is questioned. Inserted in this debate, this work has as its theme the whiteness in the sociological production on racial relations in Brazil and seeks to analyze the whiteness of Florestan Fernandes (1920-1995) in the work “The integration of the black in class Society” - Vol. 1 (1965). Faced with this, the following specific objectives are unfolded: theoretically debating whiteness, establishing indicators that can help to measure it sociologically; after this, we seek to identify whether there is the presence of these indicators in the work. It is chosen to operate through the dialectical theoretical-methodological orientation, noting that concrete and objective dimensions influence and are influenced by political disputes, ideological, epistemic, etc., and that domination via superstructure becomesif the way in which the dominant group secures its dominance. Understanding counter-hegemonic knowledge as possibilities for renewal and ontological diversity, something marked by the Foucauldian perspective, by black feminism and by postcolonial and decolonial intellectuals, the theoretical contribution of Lélia Gonzalez (1935-1994) and Guerreiro Ramos (1915-1982) assists this research in a unique way, given that, at a time very close to Fernandes, they produced other views on racial issues in Brazil. Thus, the research has scientific and social objectives, contributing to the expansion of critical debates on whiteness and encouraging the potential analytical horizon of different apprehensions about racial relations in the country.